Pemberatasan Kejahatan Internasional berdasarkan Mutual Legal Assistance Treaties (MLATs) - I Nyoman Sindhu Gautama (Jurnal Aktual Justice, 2019)
The form of cooperation between countries in the practice of customary international law can be done through Mutual Legal Assistance Treaties (MLATs). This form of cooperation appears in the practice of eradicating international crimes, which are transnational or international crimes as an act of implementing other agreements, which have been carried out among the countries involved in it. Law enforcement efforts against international crimes can be carried out through extradition treaties. Apart from that, other international agreements, both bilateral and multilateral, or mutual legal assistance treaty or judicial assistance treaty between two or more countries. Mutual Legal Assistance Treaties (MLATs) also emerged because the eradication of crime was not sufficiently enforced by extradition agreements. More and more forms of Mutual Legal Assistance Treaties (MLATs) have been agreed upon, for example the United Nations Convention Against Corruption in 2003, the United Nations Conventions Against Transnational Organized Crime in 2000. Whereas at the ASEAN Regional level, the Treaty Mutual Legal Assistance in Criminal Matters in 2004. If this is well developed, especially in the State of Indonesia, then efforts and implementation in resolving these transnational problems can be overcome.